Prevalence and prognostic impact of anemia and iron deficiency in patients hospitalized in an internal medicine ward: The PRO‐IRON study. (13th October 2017) - Fonseca, Cândida; Araújo, Manuel; Moniz, Patrícia; Marques, Filipa; Araújo, Inês; Costa, Luís; Rodrigues, Joana; Frade, Luciana; Botella, Arturo; Jesus, Susana; Leitão, Ana; Campos, Luís
Abstract: Objectives: To assess prevalence, predictive factors, and prognostic impact on in‐hospital mortality of anemia, iron deficiency anemia (IDA), iron deficiency with or without anemia (ID), and iron deficiency without anemia (IDWA) in patients admitted to an internal medicine ward. Methods: This 1‐year prospective study collected data on demographics, medical history, and blood tests in 771 consecutive patients on admission. Results: Most patients were ≥65 years old (80%) and had hypertension (63%), moderate chronic kidney disease (CKD) (43%), and heart failure (41%). Prevalence of anemia, IDA, ID, and IDWA was 67%, 41%, 58%, and 18%, respectively. Anemia was independently associated with age ≥65 years (OR 1.76, 95% CI 1.15‐2.70), active cancer (OR 2.44, 95% CI 1.42‐4.39), and moderate CKD (OR 1.65, 95% CI 1.12‐2.43). ID was independently associated with female gender (OR 2.29, 95% CI 1.64‐3.22), heart failure (OR 1.65, 95% CI 1.16‐2.37), and moderate CKD (OR 2.95, 95% CI 2.04‐4.30). Incidence of in‐hospital mortality was 21% and independently associated with anemia (RR 1.82, 95% CI 1.21‐2.74). Conclusions: Anemia and iron deficiency were highly prevalent in internal medicine patients. As anemia negatively impacts on in‐hospital mortality, awareness should be raised for effective diagnosis and management of these comorbidities in hospitalized patients.